Positivity Rates of Histology Results Based on Lesion Size and Bronchus Sign in Lung Cancer - Navratilova, Melfia; Aniwidyaningsih, Wahju; Soehardiman, Dicky; Prasenohadi, Prasenohadi; Alatas, Muhamad Fahmi; Elhidsi, Mia; Desiyanti, Ginanjar Arum; Reisa, Tina; Martini, Ni Putu Laksmi Ananda (Respiratory Science, 2025)
Background: Lung cancer continues to be a major cause of cancer-related deaths globally. Bronchoscopy serves as a key diagnostic tool, allowing histological sampling through transbronchial biopsy (TBB). The bronchus sign, identified on pre-biopsy CT scans, is associated with improved diagnostic yield in TBB. Method: A retrospective study was conducted between October and December 2023 at Persahabatan Hospital, Jakarta, analyzing 88 patients suspected of lung cancer. Data collected comprised patient demographics, lesion size as determined by CT scans, and the presence or absence of the bronchus sign. Fisher’s exact test was applied for statistical analysis, with a predetermined significance level of P<0.05. Results: Positive histology results were identified in 38 cases (55.07%) for lesions ≥3 cm and 9 cases (47.39%) for <3 cm(P=0.607). In lesions ≥3 cm, the positivity rate was similar between those with the presence (55.81%) and absence (53.85%) of a bronchus sign (P>0.99). In lesions <3 cm, positivity was higher with a bronchus sign (60%) than without (25%) (P=0.55). Conclusion: The bronchus sign appears to increase TBB positivity, especially in peripheral lesions <3 cm. Lesion size also appears to influence TBB yield. However, the findings were not statistically significant, likely due to small sample size and missing CT data.